Differential Role of the T6SS in Acinetobacter baumannii Virulence - Repizo, Guillermo Daniel (2015)
Gram-negative bacteria, such as Acinetobacter baumannii, are an increasing burden in hospitals worldwide with an alarming spread of multi-drug resistant (MDR) strains. Herein, we compared a type strain (ATCC17978), a non-clinical isolate (DSM30011) and MDR strains of A. baumannii implicated in hospital outbreaks (Ab242, Ab244 and Ab825), revealing distinct patterns of type VI secretion system (T6SS) functionality. The T6SS genomic locus is present and was actively transcribed in all of the above strains. However, only the A. baumannii DSM30011 strain was capable of killing Escherichia coli in a T6SS-dependent manner, unlike the clinical isolates, which failed to display an active T6SS in vitro. In addition, DSM30011 was able to outcompete ATCC17978 as well as Pseudomonas aeruginosa and Klebsiella pneumoniae, bacterial pathogens relevant in mixed nosocomial infections. Finally, we found that the T6SS of DSM30011 is required for host colonization of the model organism Galleria mellonella suggesting that this system could play an important role in A. baumannii virulence in a strain-specific manner.